Implementation of a simple stepped frequency continuous wave target localization system comprising two antennas based on common region of sensing - Singh V.; Bhattacharyya S.; Jain P.K. (My University, 2025)
This article focuses on the two antenna-based target localization which operates on the principle of stepped frequency continuous wave radars. The detailed study of the system generated limitations for a two antenna-based target localization system toward the practical implementation is considered and consequently, a common region of sensing (CROS) has been identified. The system capability in different sense like target tracking, spatial coverage, and through the wall localization has been investigated properly and it was found that the proposed CROS-based localization scheme is an improved as well as simple method by utilizing small number of antenna, flexibility of antenna placing, less processing with higher accuracy, and the position fixing in a simple Cartesian coordinate with reference to the two antennas. © 2019 Wiley Periodicals, Inc.